Synthesis of 1,4-Disubstituted 1,2,3-Triazoles via Three Component Coupling of Alcohol, Azide and Alkynes Using CuO Nanoparticles - Mittapelly, Nagaraju; Mukkanti, Khagga; Reddy Reguri, Buchi (Asian Journal of Chemistry, 2012)
A one-pot reaction for the synthesis of 1,4-disubstituted 1,2,3-triazoles from the alcohols via copper oxide nanoparticles (nano CuO) catalyzed nucleophilic substitution of alcohol with azide, followed by azide-alkyne 1,3-dipolar cycloaddition (click reaction) is reported. 1,4-Disubstituted 1,2,3-triazoles are obtained in good to excellent yields from a variety of readily available alcohols without the need for the preactivation and isolation of the azide intermediates.